Let's get them on board: Focus group discussions with adolescents on empowering leisure engagement in Fab Labs and makerspaces - Smolarczyk, Kathrin; Mouratidis, Marios; Uhing, Sophie; Becker, Rolf; Kröner, Stephan (International Journal of Child-Computer Interaction, 2024)
Makerspaces and Fab Labs are growing in number all over the world, holding the potential to empower children and adolescents. They form an important pathway to provide young people with access to digital manufacturing technologies while fostering self-determination, collaboration, and creativity. We explore how the engagement in Fab Lab based leisure maker activities may be promoted, taking into account both the perspectives of adolescents and the potential of surrounding systems. For this, we conducted focus group discussions with N = 61 non-maker, adolescent girls and boys from 6th to 9th grade, to scrutinize hindering and promoting factors of their engagement in leisure maker activities, and to explore their preferences regarding the involvement of parents, teachers and peers while considering the ecological sustainability of the activities. A reflexive thematic analysis identified the hindering and promoting factors across different aspects of maker activities such as the purpose, location and setting, content, and learning processes. Implications for the promotion and design of maker activities, as well as implications for further research, are discussed.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Focus groups; Leisure; Maker activities; Sustainability; Youth